Climate and social studies services: Experiences from country engagements and lessons learned - Pinto, Alessandro de; Bryan, Elizabeth; Aberman, Noora-Lisa (2019)
A framework, created by a team of researchers at the International Food Policy Research Institute, supports the integrated analysis of climate change, gender, youth and nutrition.